Pengaruh Total Quality Management, Sistem PengukuranKinerja Dan Sistem Penghargaan Terhadap KinerjaManajerial(Studi Kasus pada Rumah Sakit Umum Daerah Sukoharjo) - Arsista, Windia Pixsy, Eny Kusumawati, SE, MM, Ak, CA (2016)
The purpose of this study was to determine the influence of Total Quality Management on managerial performance, the performance measurement system on managerial performance and reward system on managerial performance The research was conducted at the General Hospital of Sukoharjo.This research uses descriptive quantitative approach, because the data in the form of numbers. The samples in this study using saturated sampling method. Samples in this study as many 45 managers. This test is used in this research is multiple linear regression analysis by SPSS v.21 program. The results of this study indicate that the Total Quality Management effect on managerial performance, the performance measurement system influence on managerial performance and reward system influence on managerial performance.